2013
DOI: 10.5222/gkdad.2013.103
|View full text |Cite
|
Sign up to set email alerts
|

Complication of Right Subclavian Vein Catheterization: Superior Vena Cava Perforation

Abstract: SUMMARY Central venous catheterization is an invasive approach

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…7had to perform thoracotomy due to haemothorax in a patient, who was performed right subclavian catheter insertion under ultrasound guidance. Çelik et al (8) reported superior vena cava perforation by right subclavian venous catheter in a thoracotomy case. The BMI of the case with no history of previous surgery or radiotherapy was 21.61 kg m -2 , but the catheter could be inserted at the third attempt.…”
Section: Discussionmentioning
confidence: 99%
“…7had to perform thoracotomy due to haemothorax in a patient, who was performed right subclavian catheter insertion under ultrasound guidance. Çelik et al (8) reported superior vena cava perforation by right subclavian venous catheter in a thoracotomy case. The BMI of the case with no history of previous surgery or radiotherapy was 21.61 kg m -2 , but the catheter could be inserted at the third attempt.…”
Section: Discussionmentioning
confidence: 99%